Incidence of Melasma, Breast Pain, and Depression in Users of Combination Hormonal and Progesterone-Only Contraceptives - Wardana, Aisyah Puspa; Budihastuti, Uki Retno; Munawaroh, Siti (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective : To find out if there is a difference in the incidence of melasma, breast pain, and depression between a combination hormonal contraceptive (CHC) acceptors and a progesterone-only contraceptive. Methods : This was a comparative analytical observational research with cross-sectional research design at Pakem Health Center, Yogyakarta. One hundred twenty subjects consisted of 60 progesterone-only contraceptive acceptors and 60 CHC acceptors aged 15-49 years, duration of use of hormonal contraceptives >6 months. Measurements on melasma were clinically determined, breast pain using a Visual Analogue Scale (VAS) score, and depression using the Montgomery Asberg Depression Rating Scale (MADRS) questionnaire. Results: Chi-square test results and logistic regression in CHC acceptors are likely to experience melasma (b=1.55; CI 95%=0.08-0.55; p=0.002), breast pain (b=2.32; CI 95%=0.02-0.34; p=<0.001), and depression (b=-1.02; CI 95%=1.15-6.74; p=0.023). Conclusion : There were significant differences in the incidence of melasma, breast pain, and depression in CHC acceptors and progesterone-only contraceptives. Incidence of melasma and breast pain was higher in CHC acceptors, while depression was higher in progesterone-only contraceptive acceptors.